Efecto de la micorrización y la abonadura orgánica en el cultivo de Mashua (tropaeolum tuberosum) en la variedad amarilla tardía en la zona de Caranqui, provincia de Imbabura - Gómez Chancosa, Luis Gerardo (2015)
In the present work of investigation there was evaluated the effect of the micorrización and the organic abonadura in the culture of mashua (Tropaeolum tuberosum) in the yellow late variety in the zone Santa Lucia of Caranqui Parish, Canton Ibarra, Imbabura province, located in the coordinates: north latitude 00 º 19 ' 06,92 ", length west 78 º 07 ' 02,29 " and a height 2.324 m.s.n.m. with the aim of; to value the agronomic behavior of the culture of the mashua, to evaluate the best organic combination I pay + micorrizas, and to realize the economic analysis of the treatments in study.. Used the design of Blocks completely at random, with four repetitions and nine treatments. The total experimental area possessed 1.375,00 m2, every plot was of 25,00 m2 and one useful area of 12,00 m2. It was evaluated; height of plant, diameter of stem, number of stems, number of flowers for plant, number and weight of tubers for category (the the first, the the second and third. All the average values were analyzed statistically by means of the program Infostad in which one determined the variables by means of the analysis of variance and applying the test of Duncan's multiple range to 5 % of probability, obtaining this way the difference and statistical classification of the best treatment........